THE REPRODUCTIVE BIOLOGY OF LYRATE ASIATIC HARD CLAM (MERETRIX LYRATA) IN THE INTERTIDAL ZONE OF NAM DINH PROVINCE - Thanh, Nguyen Xuan; Thung, Do Cong (Vietnam Journal of Marine Science and Technology, 2014)
820 samples of Lyrate Asiatic hard clam (Meretrix lyrata, Sowerby 1851) were collected in the farm of coastal Nam Dinh province, from February 2012 to January 2013 for this study. The results showed that the spawning season was from mid April to early September and the peak of spawning occurred from mid May to late July. Monthly, rate of males was dominant in the population. In spawning season rate of a male/female got close to balance, ranged from 0.86 to 1.14. The first size sexual maturity of the  hard clam is over 31mm in length and over 15 gr in weight. Absolute fecundity (Fa) ranged from 1,530,000 - 4,470,000 eggs/individual.